Avatar-Mediated Interaction and Collaboration: Perceptions of Individuals with ADHD in the Metaverse Context - Marinho, Iasmim da Cruz; Ribeiro, Ailton; Vieira, Vaninha; Pestana, Maria Clara; Amorim, Ana Maria (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2025: Anais do XX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2025.7023, 2025)
The metaverse consists of a set of virtual spaces that enable interaction between people, regardless of their location. The mediation of this interaction through avatars can present challenges, especially for neurodivergent individuals, such as those with ADHD, which is the focus of this research. We collected data from real users using the focus group methodological approach, conducted on a 3D platform. Our findings highlight opportunities for improving avatars’ expressions, gestures, and emotions, as well as the design of virtual environments, aiming to minimize distractions. The insights gathered provide an empirical foundation that underscores the importance of developing more inclusive and diverse immersive virtual environments.